New Marxian Times! Reflections on the 4th ICTs and Society Conference “Critique, Democracy and Philosophy in 21st Century Information Society. Towards Critical Theories of Social Media”. - Christian Fuchs (tripleC: Communication, Capitalism & Critique, 2012)
This paper presents reflections on the conference “Critique, Democracy and Philosophy in 21st Century Information Society. Towards Critical Theories of the Information Society” that took place at Uppsala University from May 2nd-4th, 2012. About 160 participants attended the conference. It featured 15 plenary talks in seven sessions, 15 paper presentation sessions organised in 5 slots that each had 3 parallel sessions. The conference was financially supported by the Swedish Research Council and organised by Uppsala University’s Department of Informatics and Media, the ICTs and Society Network (http://www.icts-and-society.net), the European Sociological Association’s Research Network 18: Sociology of Communications and Media Research (http://www.europeansociology.org/research-networks/rn18-sociology-of-communications-and-media-research.html), tripleC – Open Access Journal for a Global Sustainable Information Society (http://www.triple-c.at), the Unified Theory of Information Research Group (UTI), Aarhus University’s Department of Information and Media Studies, the Vienna University of Technology’s Institute for Design & Assessment of Technology, and Jönköping University’s  School of Education and Communication.